Proceso de depreciación de la Propiedad, Planta y Equipo del Ministerio de Agricultura Dirección Distrital Agropecuaria Los Ríos - Gonzáles Arriaga, María José (2019)
The purpose of this case study is to know the depreciation process, identifying the problems that affect the book value and its depreciation. The methodology applied is the deductive method, based on the information collected during the interview in specific conclusions, addressed to the Warehouse and Financial Unit with objective questions to clearly identify the flaws. According to the shortcomings identified in the revaluation, it was determined that it has a price for the revaluation of vehicles; In addition, for the purposes of applying the process of scrapping and auctioning on vehicles and equipment they are deficient. It was concluded that there is a lack of application of the regulations established by law causing an erroneous value in the accounting